Reflections on Teacher Job Satisfaction: The Role of Principal Supervision, Organizational Culture, Motivation, and Compensation - Lie, Darwin; Sherly, Sherly; Dharma, Edy; Wakhyuni, Emi; Sudirman, Acai (LPPM Universitas Terbuka, 2021)
The success and failure of an organization is influenced by competent Human Resources (HRM) who are oriented towards efficiency, quality, and productivity. This research aims to determine the role of principal supervision, organizational culture, motivation, and compensation as predictors of job satisfaction. The research design used a quantitative approach to causality. To obtain research data using documentation instruments and distributing questionnaires online. The sample used in the study was 215 respondents. The basis for determining the sample is oriented towards a non-probability sampling approach using a purposive sampling formula. To examine the relationship between principal supervision, organizational culture, motivation, and compensation on job satisfaction, then the structural equation modeling (SEM) approach is used using partial least squares. Findings. In accordance with the results of the study, it was found that the supervision of the principal has a significant effect on job satisfaction. Furthermore, organizational culture has a significant influence on job satisfaction. Furthermore, motivation has a significant effect on job satisfaction. Then compensation also has a significant effect on job satisfaction. motivation has a significant effect on job satisfaction. Then compensation also has a significant effect on job satisfaction. motivation has a significant effect on job satisfaction. Then compensation also has a significant effect on job satisfaction.